Habit as Switchpoint. (June 2013) - Crook, Tom
Building on Mary Poovey's reflections, this article outlines a two-fold genealogy of habit in the context of the philosophy and practice of liberalism. One aspect relates to the word 'habit', which by the 19th century had come to mean the repetitive actions of the body and mind, thus shedding its former association with dress and collective customs. The second relates to how 'habit' functioned as a means of mediating the tensions of liberalism, three in particular: between the self and the social; between an individual's past, present and future actions; and between the role of the state and the role of self-government.